Cidade e identidade: discursividades imagético-espaciais e a construção da identidade espacial do Recife, Veneza Brasileira - Lins, Juarez Nogueira (2011)
This treatise analyzes the identitary setting called Veneza Brasileira (Brazilian Venice) which is subscribed to the discoursive materialization related to the imagetic setting (literary and mediatic) produced about the city of Recife. The main investigation of this research is to examine the way how the identitary setting called Veneza Brasileira has been constructed in the imagetic setting practices about the city of Recife in the nineteenth and twentieth centuries. This study is subscribed to the Applied Linguistics and considers the theoretical perspectives that come from the Cultural Studies which investigation basis is focused on authors such as: Hall (2006); Bauman (1999; 2001;2005); Silva (2000); and Castells (2000) related to the discussion over identity, as well as the discussion over Urban Studies presented in Santos (1997; 1999); Ferrara (1998); and Pesavento (2001). Moreover it is also based on the theoretical basis found in Foucault (2004; 2006; 2007). Furthermore theoretical-methodological approaches rely on the French Discourse Analysis (DA) found in Orlandi (2001); Gregolin (2007); and Courtine (2006). On being so, this treatise aims to: analyze the meaning effects over the production of the identitary setting, especially the so-called Veneza Brasileira, in the imagetic setting discoursive practices (Poems, Post Cards and Touristic Guides) which are produced over the urban setting of the city of Recife. This research is characterized by being qualitative and interpretative and the theoretical analytical approaches contributed to the reading of both poetic and iconic images presented in the excerpts of poems from the nineteenth century and early twentieth century in: Manuel Bandeira s poems, Carlos Pena Filho s poems, and João Cabral de Melo Neto s poems which were produced in the early and late twentieth century. Moreover, this study observed some photographic images in Post Cards and Touristic Guides related to the visiting of historical sites in Recife. One could conclude that the imagetic setting discourse about Recife produced different identitary effects over the so-called Veneza Brasileira along these three centuries: in the nineteenth century, the poetry constructed the utopia city along with the meaning effect of identitary unit; as for the twentieth century, one observed an oscillation between a utopia/heteroutopia city meaning effect of both united and fragmented identity, the latter one is prevalent. As for the twenty-first century, the media reconstructed over again the utopia city, and consequently, produced meaning effect of identitary unit. These same meaning effects of identity either corroborate or contradict to/with the concepts of the postmodernism over identity along these three centuries. In other words, considering the imagetic setting, this oscillation occurs in the proportion of one finds an (ex) inclusion of social agents that construct these same identities.